(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The widespread belief is that fair methods are the best assurance of fair outcomes. Making and enforcing decisions following fair procedures is what procedural justice is all about. People feel validated when procedures treat them with respect and dignity, making it simpler for them to accept even unfavorable outcomes. Additionally, Criminal justice is the process of bringing persons who have committed crimes to justice. A multitude of government departments and organizations make up the criminal justice system. The rehabilitation of offenders, the prevention of other crimes, and spiritual assistance for victims are all goals. Though there are many governmental institutions which are working on assuring justice the crime victim get their remedies, but for a basic guidelines and awareness, it is necessary to know the basic legal structure of the criminal law. So the primary objective is to clarify and demonstrate the role of the criminal law to assure Public Justice under the comparative global legal frame.